2019
DOI: 10.3233/jad-190165
|View full text |Cite
|
Sign up to set email alerts
|

Episodic-Memory Performance in Machine Learning Modeling for Predicting Cognitive Health Status Classification

Abstract: Background: Memory dysfunction is characteristic of aging and often attributed to Alzheimer's disease (AD). An easily administered tool for preliminary assessment of memory function and early AD detection would be integral in improving patient management. Objective: Our primary aim was to utilize machine learning in determining initial viable models to serve as complementary instruments in demonstrating efficacy of the MemTrax online Continuous Recognition Tasks (M-CRT) test for episodicmemory screening and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…As a consequence, the incidence of AD has been reported to be higher in those individuals with lower education (16). Previous studies showed that digital health data, cognitive performance such as memory, and neuropsychiatric symptoms can help identify those with dementia from normal subjects (17)(18)(19)(20)(21). Some research groups (19) have suggested that a diagnosis of dementia can be made from health recording data.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the incidence of AD has been reported to be higher in those individuals with lower education (16). Previous studies showed that digital health data, cognitive performance such as memory, and neuropsychiatric symptoms can help identify those with dementia from normal subjects (17)(18)(19)(20)(21). Some research groups (19) have suggested that a diagnosis of dementia can be made from health recording data.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation and demonstrated utility of MemTrax and these models in China, where the language and culture are drastically different from other regions of established utility (e.g., France, Netherlands, and United States) [ 7, 8, 27 ], further underscores the potential for widespread global acceptance and clinical value of a MemTrax-based platform. This is a demonstrable example in striving toward data harmonization and developing practical international norms and modeling resources for cognitive screening that are standardized and easily adapted for use worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, valid clinical diagnoses and costly procedures for advanced imaging, genetic profiling, and measuring promising biomarkers are not always readily available or even feasible for many providers. Thus, in many instances, initial overall cognitive health status classification may have to be derived from models using other simple metrics provided by the patient (e.g., self-reported memory problems, current medications, and routine activity limitations) and common demographic features [ 7 ]. Registries such as the University of California Brain Health Registry (https://www.brainhealthregistry.org/) [ 27 ] and others with an inherent greater breadth of self-reported symptoms, qualitative measures (e.g., sleep and every day cognition), medications, health status, and history, and more detailed demographics will be instrumental in developing and validating the practical application of these more primitive models in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations